The Defensive Action of LYRM03 on LPS-Induced Acute Lung Injury by NF-κB/TLR4/NLRP3 Signals - Bin Wang; Jiaoyue Wang; Daopeng Lu; Na Qi; Qin Liu (Journal of Investigative Surgery, 2021)
The aim of the current investigation was to study the role of 3-amino-2-hydroxy-4-phenyl-valyl-isoleucine (LYRM03) in lipopolysaccharide (LPS)-induced acute lung injury (ALI) and investigate its potential pathogenesis. An LPS-induced ALI model was produced with LPS (5 mg/kg) followed by 24 h of injury. Rats were randomly assigned to 6 groups for in vivo experiments: (1) Sham, (2) LYRM03 (20 mg/kg), (3) LPS, (4) LPS plus LYRM03 (5 mg/kg), (5) LPS plus LYRM03 (10 mg/kg), and (6) LPS plus LYRM03 (20 mg/kg). The rat alveolar macrophage cell line (NR8383) cells were divided into 6 groups for in vitro experiments: (1) Sham, (2) LYRM03 (200 μmol/L), (3) LPS (100 ng/mL), (4) LPS plus LYRM03 (50 μmol/L), (5) LPS plus LYRM03 (100 μmol/L), and (6) LPS plus LYRM03 (200 μmol/L). Further study about siRNA targeting NF-κB p65, TLR4, and NLRP3 to explore the potential mechanism of LYRM03 in the LPS-induced ALI models have been done. Therefore, LYRM03 decreased LPS-induced ALI and NR8383 activation as demonstrated through hematoxylin-eosin staining and western blot analysis in vivo and in vitro. LYRM03 ameliorated the content of protein in bronchoalveolar lavage fluid, myeloperoxidase in the lung and malondialdehyde (MDA) in serum. In addition, LYRM03 ameliorated the levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-18 (IL-18) in the serum of rats and the supernatant of NR8383 cells. Moreover, LYRM03 significantly inhibited the activities of nuclear factor kappa B (NF-κB), myeloid differentiation factor 88 (MyD88), and toll-like receptor 4 (TLR4). LYRM03 also reduced the increase in the inflammasome, including apoptosis-related speck-like protein containing CARD (ASC), and NOD-like receptor 3 (NLRP3), in LPS-stimulated rats and NR8383 cells. The extent of injury and lung injury scores in the LYRM03 (20 mg/kg) + siRNA targeting NF-κB p65, TLR4, or NLRP3 + LPS-treated rats were higher than that in the LYRM03 (20 mg/kg) + LPS-treated rats. In summary, LYRM03 conferred an intensely lung defensive action on LPS-induced ALI in vivo and in vitro, which could be associated with the abatement of TLR4-induced NLRP3/NF-κB.